Reinterpreting Uang Panai: Between Cultural Values and Social Burdens through Ṭāhir Ibn ʿĀshūr's Maqāṣid al-Sharīʿah - Muh. Ishak, Andi; Sumbulah, Umi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
Uang panai is a customary marriage tradition among the Bugis community that embodies symbolic values of respect, sincerity, and the prospective groom's responsibility toward the prospective bride. However, contemporary social transformations have gradually altered its original meaning, turning uang panai into an economic burden that may hinder marriage. This study examines the practice of uang panai as a reflection of the tension between cultural values and burdensome tradition through a thematic analysis of the Qur'an from the perspective of Ṭāhir Ibn ʿĀshūr's maqāṣid al-sharīʿah. Employing a qualitative case study approach, the research combines descriptive-analytical methods with a thematic examination of Qur'anic verses concerning marriage, justice, facilitation, and public welfare (maṣlaḥah). The findings indicate that the Qur'an consistently emphasizes the principles of ease (taysīr), justice (ʿadl), and the prevention of harm in the institution of marriage. From the perspective of Ṭāhir Ibn ʿĀshūr's maqāṣid al-sharīʿah, social customs are considered legitimate only insofar as they remain consistent with the higher objectives of Islamic law, particularly the protection of lineage, property, and social harmony. Accordingly, the practice of uang panai should be critically reinterpreted and proportionally reconstructed so that its cultural significance can be preserved while remaining aligned with the objectives of the Sharīʿah and the ethical spirit of the Qur'an.